Pengungkapan Environmental Social Governance (ESG) Terhadap Nilai Dan Kinerja Perusahaan di Indonesia - Anita, Anita; Hernawati, Erni; Rossa, Vidya Dharma (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2025)
Environmental social governance (ESG) is a criterion used to measure the sustainability of a company and is often a reference for investors in choosing investor decisions because companies with good ESG tend to have good performance. This research aims to determine the effect of environmental social governance (ESG) disclosure on company value and company performance in Indonesia. Researchers use secondary data sources in the form of financial reports with data collection techniques, namely documentation. The population of this research is 22 companies listed on the IDX that have the highest ESG scores in the 2021-2023 period with a total sample of 54 data. The sampling technique uses purposive sampling. The data analysis method used in this research is a quantitative analysis technique with multiple regression hypothesis testing, which is processed with the help of the Statistical Product and Service Solution (SPSS) data processing software program version 25. The results of hypothesis testing show that environmental social governance (ESG) is not effect on firm value, and environmental social governance (ESG) also has no effect on company performance in Indonesia.